2004
DOI: 10.1128/mcb.24.1.306-319.2004
|View full text |Cite
|
Sign up to set email alerts
|

Snail Mediates E-Cadherin Repression by the Recruitment of the Sin3A/Histone Deacetylase 1 (HDAC1)/HDAC2 Complex

Abstract: The transcription factor Snail has been described as a direct repressor of E-cadherin expression during development and carcinogenesis; however, the specific mechanisms involved in this process remain largely unknown. Here we show that mammalian Snail requires histone deacetylase (HDAC) activity to repress E-cadherin promoter and that treatment with trichostatin A (TSA) is sufficient to block the repressor effect of Snail. Moreover, overexpression of Snail is correlated with deacetylation of histones H3 and H4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
587
5

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 667 publications
(636 citation statements)
references
References 57 publications
30
587
5
Order By: Relevance
“…Therefore, it is not difficult to understand why siSnail, but not siYY1 dissociated EZH2 and HDAC1/2 from the YY1 region of Ecadherin promoter. As a result of our collective present data, together with other group's findings (van der Vlag and Otte, 1999;Peinado et al, 2004;Herranz et al, 2008;von Burstin et al, 2009), herein we propose a main co-repressor complex, that is, EZH2/HDAC1/2/Snail, in the regulation of E-cadherin in NPC cells, and probably in a number of other types of human cancers. A schematic representation of the major molecular mechanisms of this complex, in NPC cells, is suggested and provided in Figure 5d.…”
Section: Ezh2 Promotes Npc Cell Aggressiveness Z-t Tong Et Alsupporting
confidence: 84%
See 1 more Smart Citation
“…Therefore, it is not difficult to understand why siSnail, but not siYY1 dissociated EZH2 and HDAC1/2 from the YY1 region of Ecadherin promoter. As a result of our collective present data, together with other group's findings (van der Vlag and Otte, 1999;Peinado et al, 2004;Herranz et al, 2008;von Burstin et al, 2009), herein we propose a main co-repressor complex, that is, EZH2/HDAC1/2/Snail, in the regulation of E-cadherin in NPC cells, and probably in a number of other types of human cancers. A schematic representation of the major molecular mechanisms of this complex, in NPC cells, is suggested and provided in Figure 5d.…”
Section: Ezh2 Promotes Npc Cell Aggressiveness Z-t Tong Et Alsupporting
confidence: 84%
“…Additionally, we observed that in NPC cells, the repressive function of EZH2 toward the E-cadherin was dependent on HDAC activity. Other groups previously reported that Snail mediates E-cadherin repression by the recruitment of the Sin3A/ HDAC1/2 complex (Peinado et al, 2004), and E-cadherin is suppressed by a Snail/HDAC1/HDAC2 complex to regulate metastasis of pancreatic cancer in vivo (von Burstin et al, 2009). These results, taken together, prompted us to ask (1) whether or not EZH2, the core member of PRC2, acts as a co-repressor complex with HDAC1/2 and Snail to repress E-cadherin in NPC cells, and (2) if so, in which fashion does these components interact each other.…”
Section: Ezh2 Promotes Npc Cell Aggressiveness Z-t Tong Et Almentioning
confidence: 98%
“…The best known factor regulating EMT is Snail; hence, great effort has been focused on describing the signaling and transduction pathways that regulate its activity. It has been reported that Snail regulates the cdh-1 locus when it is associated with SIN3A, HDAC1, and HDAC2 [63].…”
Section: The Epithelium To Mesenchymal Transitionmentioning
confidence: 99%
“…Both TGF-b1-stimulated parental PANC-1 cells and (unstimulated) PANC-1-ALK5-TD clones displayed a reduced expression of epithelial markers, such as E-cadherin ( Figure 5b) and cytokeratin 18 (not shown), and a concomitant increase in mesenchymal markers N-cadherin and vimentin. Expression of the EMT-associated transcription factor Snail, which is a transcriptional repressor of E-cadherin (Peinado et al, 2004), was elevated in ALK5-TD pools, albeit moderately, likely reflecting induction in some clones but not in others (Figure 5b). Of note, the kinase-active RImL45 mutant was unable to induce these changes (Figure 5b).…”
Section: Tgf-b Receptor Type I In Tgf-b-induced Tumor Suppressionmentioning
confidence: 99%